Analysis of Risk Mitigation Strategies for Problem Murabahah Financing at Baitul Mal Wa Tamwil (BMT) - Salsabila, Salsabila; Syera Fazza Fatihahdewi; Dwi Yudha Darmawan (Journal of Economic and Business Analysis, 2025)
Murabahah financing is the main product offered by Baitul Maal wa Tamwil (BMT) and is believed to have a lower risk compared to other types of financing. However, BMT often experiences problems with late payments made by its members, which can affect the liquidity and financial stability of the institution. This study aims to identify various factors that cause late payments and design effective strategies to reduce risk. The results of the analysis show that there is a significant positive influence of the factors causing late payments on the time of the delay itself, while risk mitigation strategies do not show a significant impact. These findings indicate the need for improvements in risk mitigation techniques and members' understanding of payment obligations so that the quality of financing and operational stability of BMTs are maintained.